MAKNA GERAKAN SOSIAL MEME â€œJOKOWI: THE KING OF LIP SERVICEâ€ PADA AKUN INSTAGRAM BEM UI - Sibaweh, Nurdin; Cangara, Hafied (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2021)
Along with the development of technology and the emergence of new media, the form of social movement has also developed into not only physical action and mass movements on the street, but it has turned into new kind of actions with more varied forms of movement.Â  such as movement through social media and memes on Instagram. On June 26, 2021, BEM UI through @bemui_official instagram account, had brought up the meme "Jokowi: The King of Lip Service" which went viral in cyberspace, this meme managed to attract reactions from related parties and also gained a wide response from the public. This study aims to examine the meaning of the socio-political movement of the meme "Jokowi: The King of Lip Service" uploaded by the BEM UI Instagram account, using an interpretive paradigm and a qualitative-descriptive approach. Ferdinand de Saussure's semiotic theory is used to analyze the case through its main model, the signifier and the signified. The results showed that the meme represented a student social movement to criticize President Jokowi for the inconsistent words, attitudes and policies issued. This inconsistency is shown, among others, in the case of weakening the KPK, the revision of the UU ITE, repressive actions against demonstrators, and the intercept of a lawsuit against the UU Cipta Kerja.Keywords: BEM UI, Social movement, Instagram, Jokowi. Â